AB0511 Does the Advanced AGE Influence on the Type of Renal Injury and the Prognosis of Lupus Nephritis?. (10th June 2014) - Armengol, E.; Narvaez, J.; Borrell, H.; Heredia, S.; Ricse, M.; Benavent, E.; Roset, A.; Gomez Vaquero, C.; Torras, J.; Mitjavila, F.; Nolla, J.M.
Abstract : Objectives: To analyze if the advanced age influence on the type of renal injury and the prognosis of lupus nephritis (LN). Methods: We evaluated 243 patients with systemic lupus erythematosus (SLE) followed in our department from 1980 until 2013 that were registered in a specific data basis (register AQUILES). Patients with biopsy-proven LN and 2 years of time tracking (n=79) were selected as the study population. We realize a comparative study between patients older (n=30) and younger (n=49) than 50 years old. In the evaluation of the response, we considered "responders" those patients who were in remission (partial or complete) after complete the induction treatment and "non responders" those who did not showed improvement in the analytics, as well as in those who we proved transformation of histologyc class and those who died by nephritis-related reasons. To compare between groups with continuous variables we had used the Student's t test and Mann – Whitney U test (on non-normal distributions). To compare categorical variables we used c hi -square test and Fisher's exact test when sample sizes were small than 5. The significance level was established for p value under 0.05. Results: The cohort included 79 patients (64 females) with a mean age at LN diagnosis of 45±14 (rank, 17-80) years and mean LN disease duration of 15.9 months (rank, 0 - 456). 81% (64/79) of patients presented renal disease at LN diagnosis or during the first year of tracing. The mean SLEDAI score was 15±7.6. The comparative study results between age groups are showed at table 1. We did not note significant differences between groups in evolution course neither in the prognosis of SLE. About the treatment, we did not detect significant differences in the percentage of patients who get hydroxychloroquine, glucocorticoids or immunosuppressant drugs, but we found differences in a higher use of statins (p=0.038) and ACE inhibitors (p=0.033) in the elderly group of patients. Conclusions: The advanced age does not determine the type of renal injury and the prognosis of lupus nephritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5048